Childhood socioeconomic circumstances and disability trajectories in older men and women: a European cohort study. (23rd August 2018) - Landös, Aljoscha; von Arx, Martina; Cheval, Boris; Sieber, Stefan; Kliegel, Matthias; Gabriel, Rainer; Orsholits, Dan; van der Linden, Bernadette W A; Blane, David; Boisgontier, Matthieu P; Courvoisier, Delphine S; Guessous, Idris; et al.
Abstract: Background: We observed a lack of population-based longitudinal research examining the association of disadvantaged childhood socioeconomic circumstances (CSC) and disability [activities of daily living (ADL) and instrumental activities of daily living (IADL)] in older age, and whether socioeconomic attainments in adulthood can compensate for a poor socioeconomic start in life. Methods: Data on 24 440 persons aged 50–96 in 14 European countries (Survey of Health, Ageing and Retirement in Europe) were used to measure the associations between CSC and limitations with ADL and with IADL, using mixed-effects logistic regression models. Models stratified by gender were adjusted for education during young adulthood, main occupation during middle age, ability to make ends meet during old age and potential confounding and control variables. Results: Risks of ADL and IADL limitations increased with age and were different between women and men. For women, a gradient across CSC strata was observed, showing that the more disadvantaged the CSC, the higher the risk of ADL and IADL limitations in old age, even after adjustment for adult socioeconomic indicators. For men, the association between CSC and disability was mediated by the main occupation in middle age and the ability to make ends meet at older age. Conclusion: Women who grew up in socioeconomically disadvantaged households were at higher risk of disability in older age and this disadvantage was not attenuated by favourable adult socioeconomic conditions. Men were more likely to make up for a disadvantaged start in adulthood.